Multipartite monogamous relations for entanglement and discord - Ferreira, Jonhy S. S.; Filenga, Davi [UNESP]; Cornelio, Marcio F.; Fanchini, Felipe F. [UNESP] (Amer Physical Soc, 2018)
The distribution of quantum correlations in multipartite systems plays a significant role in several aspects of quantum information theory. While it is well known that these quantum correlations cannot be freely distributed, the way that they are shared in a multipartite system is an open problem even for a small set of qubits. Based on monogamylike relations between entanglement and discord for n-partite systems, we show how these correlations are distributed in general, determining distinct equalities and inequalities to the quantum discord and the entanglement of formation for arbitrary multipartite pure states.